DETERMINANTS OF RURAL POVERTY AND ITS PERSISTENCE IN GHANA - Jatoe, J-B; Al-Hassan, R. M. (UDS International Journal of Development, 2019)
Waging a successful fight against poverty requires being able to identify its nature and causes in specific situations, over both space and time. The study investigates the determinants of rural poverty by location for three consecutive rounds of the Ghana Living Standards Survey (GLSS) between 1998 and 2013, using mixed methods. It also estimates the effects of a household’s access to productive assets on its welfare or poverty status, and assesses why poverty and inequality persist, and the role of agriculture in that process. We find that irrespective of location, increasing dependency ratio and female headship of households reduce the likelihood of being moderately poor or non-poor relative to being poor. But education of household head at post-basic level increases the likelihood of the household being non-poor or moderately poor compared to being poor. We conclude that the determinants of poverty may vary by location; but access of households to productive assets is key to fighting rural poverty. Also, evidence from the GLSS data confirms public perceptions on poverty and inequality, and rural households in Northern Ghana are more likely to be poor. In the short to medium term we recommend providing access to productive assets for rural households; promoting family planning education and removing barriers to education, that constrain progression beyond basic education would be more effective for fighting poverty in the medium to long term. Key words: Rural poverty, Inequality, Persistence, Determinants of poverty, Mixed methods